2014
DOI: 10.4103/2141-9248.133467
|View full text |Cite
|
Sign up to set email alerts
|

Who guards the guards: Drug use pattern among medical students in a Nigerian University

Abstract: Background:Several studies have examined the prevalence and pattern of substance use among medical students in Nigeria. Few of these studies have specifically examined the relationship between the psychological distress and psychoactive substance use among these students. Yet, evidence world-wide suggests that substance use among medical students might be on the rise and may be related to the level of stress among them.Aim:The present study is the first study aimed to determine the prevalence, pattern and fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
8
24
1
Order By: Relevance
“…This study showed that the majority of students started using drugs in middle -late adolescents, while still in secondary school. This is consistent with the findings from other studies [29,[31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that the majority of students started using drugs in middle -late adolescents, while still in secondary school. This is consistent with the findings from other studies [29,[31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…Most studies conducted in America, Europe, Australia, and Africa reported use of NPS (amphetamine, benzodiazepines, hallucinogens, and ketamine) and illicit drugs (LSD, Ecstasy, heroin, cocaine, and crack) [ 14 – 18 ]. However in our study we didn’t find use of NPS, the illicit drugs, and the non-existent drug Relevin.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that 2.8% of university students in Eldoret Kenya used Marijuana [ 13 ]. There are also other surveys which are done at Nigeria, Central America, Europe, Australia, and Dominican Republic depicting the use of other illicit drugs and NPS [ 14 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like studies by Babalola in Nigeria, Damiral in Turkey and Hull SK in Ohio, USA. 8,9,10 Kjeldstadli after a cohort study has concluded the same result and suggested encouraging medical students to spend more time for personal and social life. 11 A crosssectional study by Gharavi in Iran suggested stress management training for medical students because of high levels of stress.…”
Section: Introductionmentioning
confidence: 79%